Furry Friends : Marshmallow Magic - Webb, Holly; Elsom, Clare (London : Scholastic Children's Books, 2017)
Sophie loves her new guinea-pig friend Josephine. But then she meets Josephine's sister, Angelique, who is not nearly as friendly. In fact, the other guinea pig is positively mean! Can Sophie win over Angelique and show her that being friends with a human can be fun?
3-6.
Keywords: Friendship -- Fiction